2014
DOI: 10.1002/2014jc010061
|View full text |Cite
|
Sign up to set email alerts
|

Polar Front around the Kerguelen Islands: An up‐to‐date determination and associated circulation of surface/subsurface waters

Abstract: The circulation of iron-rich shelf waters around the Kerguelen Islands plays a crucial role for a climatically important, annually recurrent phytoplankton spring bloom over the sluggish shelf region and its downstream plume area along the Antarctic circumpolar flow. However, there is a long-standing confusion about the Polar Front (PF) in the Kerguelen region due to diverse suggestions in the literature for its geographical location with an extreme difference over 10 of latitude. Based on abundant historical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(182 citation statements)
references
References 25 publications
12
170
0
Order By: Relevance
“…Studies conducted during KEOPS1 showed a decoupling of the seasonal use of nitrate and silicic acid stocks over the Kerguelen Plateau (Mosseri et al, 2008), although Si : NO 3 assimilation ratios were close to 1, in accordance with what is expected for non-limiting iron conditions (Takeda, 1998; Park et al (2014). The inset picture gives indication about surface chl a (colour scale), surface velocity fields (arrows), and the polar front (PF, black line).…”
Section: A J Cavagna Et Al: N Cycling In the Vicinity Of Kerguelensupporting
confidence: 70%
See 2 more Smart Citations
“…Studies conducted during KEOPS1 showed a decoupling of the seasonal use of nitrate and silicic acid stocks over the Kerguelen Plateau (Mosseri et al, 2008), although Si : NO 3 assimilation ratios were close to 1, in accordance with what is expected for non-limiting iron conditions (Takeda, 1998; Park et al (2014). The inset picture gives indication about surface chl a (colour scale), surface velocity fields (arrows), and the polar front (PF, black line).…”
Section: A J Cavagna Et Al: N Cycling In the Vicinity Of Kerguelensupporting
confidence: 70%
“…1). Moreover, a third condition impacting productivity is the proximity of the polar front, the trajectory of which is steered by the bottom topography (Park et al, 2014). Such a frontal system by itself offers peculiar conditions inducing significant biological activity (de Baar et al, 1995).…”
Section: A J Cavagna Et Al: N Cycling In the Vicinity Of Kerguelenmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved iron (dFe) is delivered to the mixed layer through two processes: winter mixing and entrainment of dFe from deeper waters and, to a less extend, vertical diapycnal diffusion of dFe in summer (Bowie et al, 2015). South of the Kerguelen Island, the polar front is permanent and non motile (Park et al, 2014) and therefore does not impact sediment trap deployment location. At the A3 station, the circulation is weak (o3 cm s À 1 ) and primarily tidal-driven (Park et al, 2008).…”
Section: Sediment Trap Deployment and Environmental Datamentioning
confidence: 99%
“…Detailed descriptions of the complex physical structure of the area, circulation, water masses and fronts are given in Park et al (2014). Briefly, the main hydrodynamic features observed during the cruise are the following (see θ − S diagram, Fig.…”
Section: Study Areamentioning
confidence: 99%